History of extracorporeal interventions on kidneys and renal arteries - A. E. Zotikov; A. S. Ivandaev («REMEDIUM GROUP» Ltd., 2020)
Extracorporeal surgery on kidneys and renal vessels is an unfamiliar field of surgery for the medical community. This surgical approach involves performing surgery on an organ outside the body or, in other words, ex vivo. However, such interventions have several undeniable advantages in special clinical situations. These include: kidney ischemia, better visualization, work in a bloodless area and almost unlimited time, safe for kidney function. However, despite all the advantages of this surgical approach, it is not widely used in everyday clinical practice due to the technical complexity of the surgery. As a result of the analysis of the available literature, it is clear that these surgeries can be effective in a wide range of diseases. The problem of radical surgical treatment is especially acute when the standard approach is not possible, when the operation is performed in situ. In such cases, the performance of extracorporeal surgery with subsequent kidney autotransplantation allows to perform radical treatment in case of particularly pronounced damage to the kidney and/or its vessels.A review of literature is given, which presents the history of formation and development of extracorporeal surgeries on kidneys and renal vessels. Experimental extracorporeal interventions with kidney autotransplantation and clinical observations are chronologically described in the article. Literal data on the performance of extracorporeal surgeries in a wide range of different diseases are summarized. The domestic and foreign experience of such interventions is reflected as widely as possible. The stages of development of extracorporeal renal surgery from the first clinical observations to the present day are described. The distant results of the largest researches indicating appropriateness, expediency and validity of performance of similar surgeries are given. Particular relevance of this surgical technique is acquired when the standard, intracorporeal intervention is unavailable. Thus, the use of extracorporeal surgery technique allows to expand the possibilities of providing surgical assistance to patients with various pathologies of the kidneys and/or renal vessels.